Educational social networking services: The case of edmodo in the teaching practice - Nafsika, Tegousi; Vasileios, Drakopoulos (Trends in Computer Science and Information Technology, 2020)
In recent years, there has been a strong education interest in second generation World Wide Web (Web 2.0) applications such as blogs, social networking, information sharing tools, social bookmarking and more. This article presents a case of using an online social learning network offering communication, collaboration and coaching tools to K-12 schools and teachers as well as a means of communication among pupils themselves. Given the students’ familiarity with computers and the internet, it was considered that using these tools in teaching would motivate them during the lesson, and, in particular, it would benefit the weakest students who often maintain a non-positive attitude towards the traditional (conventional) face-to-face lesson. In order to achieve this goal, Edmodo has been selected from all the available as a technology based educational learning tool, thanks to the ability of using the Greek language since the summer of 2011. The features of this social learning tool and the experience of using it in Secondary Education within the course “Informatics Applications” are reported here: during one school year, and some examples of its use in everyday teaching. The advantages of using it both pedagogically and practically, as well as some problems encountered by students and teachers during their practicum studies, are presented. The purpose of this article is to present in general terms the use of the Edmodo platform in the course of Informatics in a real class of the Evening Vocational Lyceum (EPAL).